Religious rivalries in the early Roman Empire and the rise of Christianity - Vaage, Leif E. (Studies in Christianity and Judaism, 2006)
Religious Rivalries in the Early Roman Empire and the Rise of Christianity discusses the diverse cultural destinies of early Christianity, early Judaism, and other ancient religious groups as a question of social rivalry. The book is divided into three main sections. The first section debates the degree to which the category of rivalry adequately names the issue(s) that must be addressed when comparing and contrasting the social "success" of different religious groups in antiquity. The second is a critical assessment of the common modern category of "mission" to describe the inner dynamic o.